INCENTIVIZING ATTENDANCE TO PROLONGED EXPOSURE FOR PTSD IN OPIOID USE DISORDER PATIENTS: A RANDOMIZED CONTROLLED TRIAL - Schacht, Rebecca L. (J Consult Clin Psychol, 2017)
OBJECTIVE: To determine whether contingent monetary incentives increase opioid use disorder patients’ attendance to Prolonged Exposure (PE) therapy and whether attendance is associated with improvement in posttraumatic stress disorder (PTSD) and substance use disorder (SUD) outcomes. METHOD: Patients (N = 58) with PTSD were offered PE or PE with incentives (PE+I; max $480) to attend PE sessions. Participants were assessed at baseline and weeks 6, 12, and 24 post-randomization. RESULTS: Participants were mostly women (79%) and Caucasian (71%); mean age 37.43 years (SD = 11.33). PE+I participants attended a median of 9 (of 12) sessions compared to 1 session for PE participants (p < 0.001), which included more exposure sessions (PE+I mdn = 6; PE mdn = 0; p < .001). A time × treatment condition interaction indicated that PE+I participants exhibited a greater decrease in PTSD severity over time than PE participants (OR = 3.1; 95% CI = 0.4–5.7; p = 0.024). PE+I participants remained in substance use treatment longer than PE participants (mdn days = 262 vs. 192; p = 0.039). There were no group differences in drug use. CONCLUSIONS: Monetary incentives increased SUD patients’ attendance to an otherwise poorly-attended treatment for PTSD. Better attendance in the incentivized group was associated with greater PTSD improvement, better SUD treatment retention, and no increased drug use. Incentives are well supported for improving adherence to substance use treatment goals and promising as a means to improve therapy attendance, which may improve the effectiveness of existing psychotherapies in difficult-to-treat populations.